International orders in the early modern world : before the rise of the West - Quirk, Joel; Suzuki, Shogo , 1975-; Zhang, Yongjin (The new international relations series, 2014)
"This book examines the historical interactions of the West and non-Western world, and investigates whether or not the exclusive adoption of Western-oriented 'international norms' is the prerequisite for the construction of international order"-- Provided by publisher